The effects of training history, player position, and body composition on exercise performance in collegiate football players - Miller, T. A.; White, E. D.; Kinley, K. A.; Congleton, J. J.; Clark, M. J. (The Journal of Strength and Conditioning Research, 2002)
Performance data for 261 NCAA Division 1A collegiate football players were analyzed to determine if player position, body weight, body fat, and training time were correlated with changes in performance in the following events: power clean (PC), bench press (BP), squat (SQ), vertical jump (VJ), 40-yd dash (40yd), and 20-yd shuttle (20yd). Individual positions were combined into the following groups: (A) wide receivers, defensive backs, and running backs, (B) linebackers, kickers, tight ends, quarterbacks, and specialists, and (C) linemen. Increases in body weight were positively correlated with increases in BP and PC performance for all groups. Increases in body fat were negatively correlated with performance in the PC and VJ for all groups. For group C, increases in body fat were also negatively correlated with performance in the 40yd and 20yd. Group and training time exhibited no linear relationship with performance in any of the tested events. No linear relationships were observed between the independent variables and performance in the SQ. When individual training data were analyzed longitudinally, a nonlinear increase in performance in the PC, BP, and SQ was observed as training time increased, with the greatest rate of change occurring between the first and second semesters of training.